Manajemen SumberDaya Manusia dalam Meningkatkan Mutu Pendidik pada Lembaga Pendidikan Islam - Fauzi, Rifan Anas; Rofiq, Ainur; Wafa, Ali (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to analyze the role of human resource management (HRM) in improving the quality of educators in educational institutions. The research employs a qualitative approach with data collection techniques including in-depth interviews, observations, and document studies. The subjects of the study include HR managers, school principals, and educators in several educational institutions in Indonesia.The findings indicate that HRM plays a significant role in enhancing the competencies and performance of educators. In conclusion, effective HRM is key to enhancing the quality of educators in educational institutions. The implications of this study suggest that educational institutions should adopt holistic HRM practices that focus on the continuous development of educators to achieve higher educational goals.